Investigations into magnetic relaxation for vanadium complexes - Jackson, Cassidy Elizabeth, author; Zadrozny, Joseph M., advisor; Shores, Matthew P., committee member; Chen, Eugene, committee member; Ross, Katherine, committee member (Colorado State University. Libraries, 2022)
Magnetic molecules represent an emerging class of complexes that can be used to understand quantum phenomena impactful for quantum computing, non-invasive magnetic resonance imaging, and information storage. These organometallic complexes have the electronic spin is centered on the metal ion. Magnetic molecules based on electronic spins are extremely sensitive to changes in their local environment, such as nuclear spins. Electronic spins on a metal ion were employed to understand how nuclear spins in the local environment modulate electron spin dynamics. In this work, vanadium(IV) was chosen to study with varying catechol ligands. Electron paramagnetic resonance (EPR) was used to study two properties of these metal complexes, spin-lattice relaxation (T1) and phase memory relaxation (Tm or T2). Investigation of these parameters and fitting of these parameters provided information of how the local environment played a role in shortening these lifetimes. The complexes developed in this work indicates that the local environment is an extremely important piece of relaxation due to drastic changes in relaxation times. Chapter 1 introduces provides motivation for the work conducted in this dissertation and gives a thesis structure overview. Chapter 2 gives a broad summary of the field of molecular magnetism and provides metaphors for the synthetic chemist to learn about electron spin relaxation. Chapters 3 gives the first report of nuclear spin patterning on a ligand shell impacting spin relaxation times Chapter 4 details high-field, high-frequency orientation dependence on spin relaxation times for the V(IV) ion. Chapter 5 explores proton nuclear spin dynamics as they relate to nuclear spin patterns on a ligand and ligand complexed to a diamagnetic metal ion. Chapter 6 explores counterion dynamics and how they impact spin relaxation times. Chapter 7 gives a summary and future directions.
Keywords: electronic spin; spectroscopy; vanadium; molecular magnetism; electron paramagnetic resonance; spin relaxation